2016
DOI: 10.1038/srep39444
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Cellular DNA Damage Response by Porcine Circovirus Type 2 Facilitates Viral Replication and Mediates Apoptotic Responses

Abstract: Cellular DNA damage response (DDR) triggered by infection of DNA viruses mediate cell cycle checkpoint activation, DNA repair, or apoptosis induction. In the present study, infection of porcine circovirus type 2 (PCV2), which serves as a major etiological agent of PCV2-associated diseases (PCVAD), was found to elicit a DNA damage response (DDR) as observed by the phosphorylation of H2AX and RPA32 following infection. The response requires active viral replication, and all the ATM (ataxia telangiectasia-mutated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
5
10
0
Order By: Relevance
“…Toledo et al proposed a tumor‐suppressive potential of ATR activation in a DNA‐damage‐independent manner by promoting cell cycle arrest . ATR activation has also been described to trigger apoptosis, and under our conditions, ATR could be involved both in proliferation arrest and apoptosis induction . Moreover, we showed that TNFα expression increased in hypoxia relative to that in normoxia and contributed to IAPs inhibition‐decreased cell viability in hypoxia as evidenced by the impaired Smac mimetic effect on cell viability caused by Enbrel.…”
Section: Discussionsupporting
confidence: 57%
“…Toledo et al proposed a tumor‐suppressive potential of ATR activation in a DNA‐damage‐independent manner by promoting cell cycle arrest . ATR activation has also been described to trigger apoptosis, and under our conditions, ATR could be involved both in proliferation arrest and apoptosis induction . Moreover, we showed that TNFα expression increased in hypoxia relative to that in normoxia and contributed to IAPs inhibition‐decreased cell viability in hypoxia as evidenced by the impaired Smac mimetic effect on cell viability caused by Enbrel.…”
Section: Discussionsupporting
confidence: 57%
“…(a) MA104 cells were either mock infected or infected with rotavirus-SA11 in the presence of DMSO, KU-55933 (10 μM), or BML-277 (10 μM), and whole cell lysates were prepared at 3 and 6 hpi. Concurrent observation of MRN-dependent ATM activation has also been reported for several viruses including MVC, MVM, HPV, PCV2, and HSV-1 Moody & Laimins, 2009;Adeyemi et al, 2010;Luo et al, 2011;Wei et al, 2016). (b, c) MA104 cells were mock infected or infected with rotavirus-SA11 in the presence of DMSO, KU-55933 (10 μM), or BML-277 (10 μM).…”
Section: Discussionsupporting
confidence: 64%
“…Averting unfavourable outcomes of such host-virus interaction has been virusinduced optimisation of DDR-a noncanonical response with multiple layers of complexity. *** p ≤ .001, unpaired t test Zhao et al, 2008;Moody & Laimins, 2009;Adeyemi et al, 2010;Luo et al, 2011;Baer et al, 2012;Wei et al, 2016). Noncanonical usurpation of DDR is how viruses ensure selective exploitation of certain DDR components while subverting others thereby mitigating untoward consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations